2017
DOI: 10.1371/journal.pone.0177884
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor blockade enables dexamethasone to inhibit lipopolysaccharide-induced murine lung neutrophils

Abstract: Glucocorticoids promote neutrophilic inflammation, the mechanisms of which are poorly characterized. Using a lipopolysaccharide (LPS)-induced acute murine lung injury model, we determined the role of granulocyte colony-stimulating factor (G-CSF) in mouse lung neutrophil numbers in the absence and presence of dexamethasone, a potent glucocorticoid. G-CSF was blocked using a neutralizing antibody. Airway neutrophil numbers, cytokine levels, and lung injury parameters were measured. Glucocorticoid treatment maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The BALF of C57BL/6 mice mostly contained eosinophils (Figure 1C), while BALB/c mice responded with a neutrophilia (Figure 1D). As expected, the neutrophilic inflammation in BALB/c was accompanied by an upregulation of G-CSF (Figure 1E) in the lungs 12 hours after the Alt treatment, consistent with the function of G-CSF in promoting the recruitment of neutrophils from the bone marrow after airway allergen challenge (27,28). Remarkably, both mouse strains showed a fast upregulation of IL-5 in the lungs after the Alt treatment (Figure 1F).…”
Section: Resultssupporting
confidence: 84%
“…The BALF of C57BL/6 mice mostly contained eosinophils (Figure 1C), while BALB/c mice responded with a neutrophilia (Figure 1D). As expected, the neutrophilic inflammation in BALB/c was accompanied by an upregulation of G-CSF (Figure 1E) in the lungs 12 hours after the Alt treatment, consistent with the function of G-CSF in promoting the recruitment of neutrophils from the bone marrow after airway allergen challenge (27,28). Remarkably, both mouse strains showed a fast upregulation of IL-5 in the lungs after the Alt treatment (Figure 1F).…”
Section: Resultssupporting
confidence: 84%
“…It was described that also other cell types such as epithelial cells, endothelial cells, fibroblasts, smooth muscle cells and macrophages can produce G-CSF. [19][20][21][22] Remarkably, the type 2-high patient with the highest elastase level (indicated in red on figure 4C), suggesting a mixed eosinophilic and neutrophilic inflammation, showed a high rate of double positive cells (90.5%), more similar to the levels of type 2-low patients.…”
Section: Neutrophils In Nasal Polyps Of Type 2-low Patients Are Posit...mentioning
confidence: 87%
“…Current treatment methods for chronic rhinosinusitis, such as glucocorticosteroids, lead to increased G-CSF levels and blocking G-CSF could thus be beneficial. 19,46 Depletion of G-CSF leads to diminished neutrophil numbers, however, several studies showed that granulopoiesis can still take place during infection and in steady state, independently of G-CSF. 47 Another possibility is targeting the receptor for G-CSF, as G-CSFR is only expressed on a limited number of cells.…”
Section: Discussionmentioning
confidence: 99%
“…After the observation that F.p. induced G-CSF and airway neutrophilia in BAL samples, a phenomenon previously observed with dexamethasone and lipopolysaccharide ( 69 ), we tested whether steroid-driven G-CSF was an important downstream mechanism contributing to airway neutrophilia by blocking G-CSF with anti–G-CSF–neutralizing mAbs (aG-CSF; Fig. 5A).…”
Section: Resultsmentioning
confidence: 85%